Eficiência da inoculação de ascósporos de Sclerotinia sclerotiorum em flores do feijoeiro na avaliação da resistência - Ferreira, Alex Naves (2022)
White mold is a disease caused by the ascomycete fungus Sclerotinia sclerotiorum (Lib.) De Bary that has a wide geographic distribution. It is a highly destructive disease that affects common bean (Phaseolus vulgaris L.) and other important crops. Although there are several methods of controlling white mold, none of them is totally effective, due to the survival of resistance structures, called sclerotia, produced by the pathogen and that survive in the soil for several years. The choice of efficient inoculation methodologies is essential in identifying sources of resistance that can be used in breeding programs, as well as in the stage of selection of progenies or resistant lines. Thus, this study was carried out with the objective of evaluating the efficiency of the methodology of inoculation with ascospore suspension in flowers in the discrimination of common bean genotypes regarding the reaction to the fungus S. sclerotiorum. The reactions of six common bean genotypes (CXII-53/10, CXII-56/6, CXII-59/8, CXII-64/9, CXII-64/14 and VC-17) to two isolates of S. sclerotiorum (UFLA 65 and UFLA 145) were evaluated using two inoculation methodologies: suspension of flowering ascospores (nebulization chamber and greenhouse) and straw test. Four controls were used: Cornell 605 and A 195 (resistant), IPR Corujinha and Beryl (susceptible) in all experiments. In the methodology of inoculation with ascospore suspension in flower, two experiments were carried out in randomized blocks: one in a greenhouse and the other in a nebulization chamber. The plot consisted of two plants per pot. Inoculation was carried out at the R6 stage of the plants, where the flower was inoculated with an ascospore suspension at a concentration of 1.5 x 106 ascospores/mL. Severity assessment was performed ten days after inoculation. In the straw test methodology, an experiment was carried out in a greenhouse in a randomized block design and the plot consisted of three plants per pot. Colonized mycelium discs were placed on the main stem of the plant with the aid of a tip, and the assessment was performed seven days after inoculation. The data obtained were submitted to analysis of variance using the Genes software and the means were compared using Dunnett's test. There was no correlation between the straw test methodology and the suspension of ascospores in flower in a nebulization chamber. The method of inoculation with ascospore suspension in flowers showed less efficiency in genotype discrimination when compared to the straw test method, but it can be an alternative in the final steps of a breeding program or when inoculation in the field is not possible.